The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/adsc.201300614
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Organolithium Generation in the Continuous Flow Synthesis of Amitriptyline

Abstract: A continuous flow protocol for the preparation of the tricyclic antidepressant (TCA) amitriptyline is reported. The advantages of flow chemistry when handling organometallic agents as well as when performing reaction with gases are demonstrated. Continuous multilithiation combined with carboxylation and the Parham cyclization, a Grignard addition and thermolytic water elimination by inductive heating are key features of the multistep protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 44 publications
0
59
0
3
Order By: Relevance
“…47 Similarly, CO 2 gas could be introduced into the stream of lithium organic intermediates, without compromising inert conditions during the continuous flow preparation of Amitriptyline. 48 Hazardous gases can be generated in situ using the aqueous solutions of their precursors in a tube-in-tube device. The highly poisonous and explosive diazomethane could be safely used in the three-step flow process to a-halo ketone building blocks of antiretroviral agents.…”
Section: Reactor Type Mattersmentioning
confidence: 99%
See 2 more Smart Citations
“…47 Similarly, CO 2 gas could be introduced into the stream of lithium organic intermediates, without compromising inert conditions during the continuous flow preparation of Amitriptyline. 48 Hazardous gases can be generated in situ using the aqueous solutions of their precursors in a tube-in-tube device. The highly poisonous and explosive diazomethane could be safely used in the three-step flow process to a-halo ketone building blocks of antiretroviral agents.…”
Section: Reactor Type Mattersmentioning
confidence: 99%
“…An elimination reaction, leading to Amitriptyline proceeded at high temperature without the use of previously employed concentrated HCl solution. 48 On a similar note, acidic conditions could be avoided in high temperature tert-butyloxycarbonyl (Boc) deprotections. 63 Highly corrosive reagents may not be suitable for a standard flow chemistry equipment and require special handling techniques and construction materials, such as a specialized dry zone for handling anhydrous HCl gas.…”
Section: Ensuring Stability For Continuous Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…They provide the benefits of ease of process automation, higher heat and mass transfer rates and a more straightforward incorporation of inline analysis tools compared to traditional batch setups. [6][7][8][9][10][11] Continuous flow systems have been used for complex chemical synthesis, [12][13][14][15] gas-phase reactions, [16][17][18][19] photochemistry, [20][21][22][23] electrochemistry, 24,25 and reaction optimization [26][27][28] but their robustness for reaction kinetics is hindered by the need to take steady state measurements. [29][30][31][32] Recent studies have shown that transient flow data could be used to quickly generate kinetic data.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, in the area of machine-assisted flow synthesis, [1] the ability to insert analogous in-line processing operations between the individual steps is essential for procedures consisting of more than one chemical transformation. [2][3][4][5][6] This requirement inspires a second design layer when planning multi-step flow procedures, which encompasses the engineering requirements for the system. This layer includes the new flexible, low cost in-line processing tools, [7][8][9][10][11] which enable some of the concepts of multi-step manufacturing processes to be applied within the research laboratory.…”
mentioning
confidence: 99%